2013
DOI: 10.1007/s11060-013-1097-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes in choroid plexus papillomas: an institutional experience

Abstract: Choroid plexus papillomas (CPPs) are rare, indolent lesions that comprise less than 0.5 % of intracranial tumors. We sought to assess the long-term outcomes and associated surgical complications at our institution. A review of the University of California, San Francisco (UCSF) Brain Tumor Research Center (BTRC) database was performed to identify a cohort of patients treated for CPP from 1997 to 2011. Patients were grouped based on tumor location and extent of resection. Outcomes including progression-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 28 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…[ 2 15 25 ] Although, a few studies have shown a higher incidence in females, the majority have shown no such predilection. [ 2 34 37 ] However, in our series, all were males in the first decade. These neoplasms present with features of raised ICP (because of hydrocephalus) or compressive effects on adjacent tissues.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…[ 2 15 25 ] Although, a few studies have shown a higher incidence in females, the majority have shown no such predilection. [ 2 34 37 ] However, in our series, all were males in the first decade. These neoplasms present with features of raised ICP (because of hydrocephalus) or compressive effects on adjacent tissues.…”
Section: Discussionmentioning
confidence: 49%
“…[ 10 17 21 25 38 ] Surgical removal is the treatment of choice, and surgical approaches need to be tailored according to the location, size, and extent of the lesion. [ 12 34 41 ] Authors report three cases of CPP in pediatric age group located in uncommon locations such as the posterior third ventricle, fourth ventricle, and CP angle. The diagnostic dilemma and management issues are discussed along with a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…14% of choroid plexus tumors occur during infancy although there are reports of third ventricle choroid plexus papilloma during 5 th decade of life (19,20). In majority of reports there is no reported sex predilection in CPTs (21,22). CPCs are almost 4 fold more common in children than adults (12).…”
Section: Discussionmentioning
confidence: 99%
“…Because of small diameters and complex neuroanatomy of third ventricle, resection of tumors in this area are challenging and highly demands expertise (32). Due to high vascularity of these tumors significant blood loss during resection should be anticipated and effectively managed specially in pediatric population (7,11,21,25). Blood loss can be limited by initial finding and securing of arterial feeders which are branches of adjacent choroidal arteries and subsequent coagulation and en-bloc or piecemeal removal of tumor bulk (7,10,24).…”
Section: Managementmentioning
confidence: 99%
“…Choroid plexus tumors (CPTs) are rare intraventricular neuroectoderm neoplasms derived from the choroid plexus epithelium 24,32,36 . According to the 2007 WHO Classification of Tumors of the Central Nervous System, primary CPTs are classified as choroid plexus papilloma (CPP, WHO grade I,80%), atypical CPP (WHO grade II,15%) and choroid plexus carcinoma (CPC, WHO grade III, less than 5%) 8,18 .…”
Section: Introductionmentioning
confidence: 99%